2012
DOI: 10.1007/s00244-012-9841-9
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicity of Cr, Cd, and Pb on Two Mediterranean Soils

Abstract: Three potentially toxic elements [chromium (Cr), lead (Pb), and cadmium (Cd)] were tested to assess their effects on two soils of different properties and origin. The soils were a granitic soil (Haplic Arenosol), which meets the requirements of OECD ecotoxicity testing, and a calcareous soil (Calcaric Regosol) with properties often found in the Mediterranean areas. The metal concentrations used ranged from 0.001 to 5,000 mg kg(-1) soil. The effects on soil microbial activity and community composition (respirom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 44 publications
0
4
0
3
Order By: Relevance
“…Therefore, microbial-induced conversion of Cr (VI) to Cr (III) leads to a reduction in toxicity, which may be a result of the precipitation of various Cr (III) chemical forms. Moreover, a toxicity has been observed even in soils containing very low contents of Cr (VI) (<1 mg kg –1 ) (Martí et al, 2013). Min et al (2017) reported that total Cr content affiliated with Cr (VI) was the major factor for the difference of soil bacterial communities.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, microbial-induced conversion of Cr (VI) to Cr (III) leads to a reduction in toxicity, which may be a result of the precipitation of various Cr (III) chemical forms. Moreover, a toxicity has been observed even in soils containing very low contents of Cr (VI) (<1 mg kg –1 ) (Martí et al, 2013). Min et al (2017) reported that total Cr content affiliated with Cr (VI) was the major factor for the difference of soil bacterial communities.…”
Section: Discussionmentioning
confidence: 99%
“…Metal bioavailability is a key factor in determining the metal’s toxicity and uptake by organisms [ 54 ] and is significantly affected by soil properties such as pH [ 48 ]. Such alkaline soil as in this case limits the presence of fractions of water-soluble soil contaminants in aqueous soil extracts [ 55 ]. Therefore, the overall PTEs bioavailability could be reduced, and the results showed decreased toxicity effect on the tested organisms.…”
Section: Resultsmentioning
confidence: 99%
“…вивчено транспорт есенціальних металів (Fe, Zn, Mn і Cu) і транспорт, толерантність, вакуолярну послідовність та рівень транскрипційних реакцій за умов дії неесенціальних металів (Cd, Pb, Cr, Hg і As), їх токсичність на рослинний гомеостаз (Mendoza-Cózatl et al, 2011;Song et аl., 2010;Takamatsu et аl., 2010). Визначено вплив Cr, Cd та Pb на середземноморські ґрунти (Martí et al, 2013) через біодоступність Cd, Pb та Zn та через атмосферні емісії Cd та Pb (Roussel et al, 2010), визначено рослинний метаболізм під впливом Cd, Co, Mn, Cr (Hameed et al, 2011;Hasan et al, 2011;Ruscitti et al, 2011;Vestena et al, 2011;Becerril et al, 2013;Lefcort et al, 2013;Millaleo et al, 2013).…”
Section: вступunclassified